2000
DOI: 10.1016/s0735-1097(99)00589-6
|View full text |Cite
|
Sign up to set email alerts
|

Atrial flutter in the perinatal age group: diagnosis, management and outcome

Abstract: Fetal AF is a serious and threatening rhythm disorder, particularly when it causes hydrops, it may be associated with fetal death or neurological damage. Treatment is required and primarily aimed at reaching an adequate ventricular rate and preferably conversion to sinus rhythm. Digoxin failed in prevention of recurrence at time of delivery in a quarter of our patients, whereas with sotalol no recurrence of AF has been reported, suggesting that class III agents may be the future therapy. Once fetuses with AF s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
80
0
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 22 publications
6
80
0
8
Order By: Relevance
“…We also demonstrated a 100% rapid response rate in the subset of patients with AF. All our findings were comparable to the success reported in other much smaller cohorts of pregnancies treated with sotalol as first-line therapy 5,11 and have demonstrated that sotalol or sotalol combined with digoxin is safe and effective first-line treatment of fetal SVTs.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also demonstrated a 100% rapid response rate in the subset of patients with AF. All our findings were comparable to the success reported in other much smaller cohorts of pregnancies treated with sotalol as first-line therapy 5,11 and have demonstrated that sotalol or sotalol combined with digoxin is safe and effective first-line treatment of fetal SVTs.…”
Section: Discussionsupporting
confidence: 90%
“…Sotalol use has typically been indicated as a second-line agent in the treatment of long VA tachycardias 5,7 and AF 6,11,12 in utero. We documented the mechanism of tachycardia in most fetuses, and although we found it of interest to have a better sense of the mechanism of therapy, our treatment strategy and the clinical outcomes with sotalol therapy were not influenced by the knowledge of the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Several transplacental therapies such as maternal administration of digitalis and antiarrhythmic drugs have been reported [1,15,16]. In our case, transplacental therapies for fetal atrial flutter were not permitted by the mother, and thus we followed the fetus carefully by ultrasonography and MCG.…”
Section: Discussionmentioning
confidence: 95%
“…Fetale Tachyarrhythmien können infolge der limitierten Reserve des fetalen Herzens zur Entwicklung eines Hydrops fetalis führen [18].Aufgrund des Druckanstieges im venösen System wird einerseits die Rückresorption der interstitiellen Flüssigkeit vermindert, andererseits der Lymphrückfluss eingeschränkt. Beide Mechanismen können in kurzer Zeit zu hydropischen Veränderungen beim Feten führen.…”
Section: Tachyarrhythmienunclassified